2012
DOI: 10.1111/ele.12009
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the impacts of emerging energy development on wildlife, with an eye towards mitigation

Abstract: Global demand for energy is projected to increase by 40% in the next 20 years, and largely will be met with alternative and unconventional sources. Development of these resources causes novel disturbances that strongly impact terrestrial ecosystems and wildlife. To effectively position ecologists to address this prevalent conservation challenge, we reviewed the literature on the ecological ramifications of this dominant driver of global land-use change, consolidated results for its mitigation and highlighted k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
227
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(229 citation statements)
references
References 95 publications
(270 reference statements)
0
227
1
1
Order By: Relevance
“…Solar energy systems are highly modular ranging from small-scale deployments (≤1 MW; e.g., residential rooftop modules, portable battlefield systems, solar water heaters) to centralized, utility-scale solar energy (USSE) installations (≥1 MW) where a large economy of scale can meet greater energy demands. Nonetheless, the diffuse nature of solar energy necessitates that large swaths of space or land be used to collect and concentrate solar energy into forms usable for human consumption, increasing concern over potential adverse impacts on natural ecosystems, their services, and biodiversity therein (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Solar energy systems are highly modular ranging from small-scale deployments (≤1 MW; e.g., residential rooftop modules, portable battlefield systems, solar water heaters) to centralized, utility-scale solar energy (USSE) installations (≥1 MW) where a large economy of scale can meet greater energy demands. Nonetheless, the diffuse nature of solar energy necessitates that large swaths of space or land be used to collect and concentrate solar energy into forms usable for human consumption, increasing concern over potential adverse impacts on natural ecosystems, their services, and biodiversity therein (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Understanding how wildlife will be affected by future industrial activities is a challenge for researchers and resource managers (Northrup and Wittemyer, 2013). Mapped output from our resource selection model clearly indicated that areas of high-value winter habitat for caribou were concentrated in valley bottoms and along ridgelines, particularly in the western reaches of the study area.…”
Section: Discussionmentioning
confidence: 94%
“…Negative environmental impacts may also occur, which could include impacts on water resources (in terms of quality and quantity for both surface water and groundwater resources) (ANU, 2012;Broomfield, 2012;Rahm and Riha 2012;Lechtenböhmer et al, 2011 andIEA, 2012), habitat fragmentation and loss (Jones and Pejchar, 2013;Northrup and Wittemyer, 2013) as well as possible increased seismicity associated with deep well wastewater injection as well as fracking operations (NRC, 2013). By identifying the possible impacts before extraction and development commences, some negative impacts during unconventional gas extraction may be minimised.…”
Section: Possible Impacts Associated With Uog Extractionmentioning
confidence: 99%